Conflicts in the Persian Gulf - Askari, H. author. aut Link
XIX, 213 p.
Keywords: This book analyzes the origins of conflicts and wars in the Persian Gulf, assesses the common factor(s) that have been their essential fuel, determines their fallout for the political, economic, and human development of the region, and provides insight into how they may be better contained.